A Mind in Training Philo of Alexandria on Jacob's Spiritual Exercises - Uusimäki, Elisa 1986- (2018)
How does Philo of Alexandria depict the formation of a wise person? This article pays attention to the centrality of spiritual training in Graeco-Roman philosophy, and argues that Philo likewise regards the process of seeking wisdom as entailing mental practice. The analysis focuses on two passages of Quis rerum divinarum heres sit and Legum allegoriarum where Philo attributes lists of spiritual exercises to the figure of Jacob. As such, these accounts illustrate how Philo makes use of scriptural interpretation as he imagines the execution of a life dedicated to wisdom. The listed exercises are largely familiar from Graeco-Roman philosophical traditions, yet they coexist with and contribute to the performance of Philo's ancestral tradition. This m?lange of cultural elements suggests that Philo discusses Jacob's inner cultivation in order to enable his audience to grasp (one prospect of) how to lead a Jewish philosophical life in the Roman Alexandria.
Keywords: Judaism as philosophy; Philo of Alexandria; philosophical training; Scriptural Interpretation; Spiritual Exercises; the figure of Jacob